4CPS-153 Intensification in biological treatment in ulcerative colitis. (24th March 2020) - Pintado, A; Asensi Diez, R; Linares, A; Muñoz Castillo, I
Abstract : Background and importance: Biological drugs have improved the therapeutic possibilities for ulcerative colitis (UC), showing good clinical efficacy. However, a considerable percentage of patient do not initially respond to treatment or lose the response achieved over time. To resolve treatment failure, several strategies have been used, including intensification of treatment. Aim and objectives: To analyse the use of biological drugs in patients with UC and the strategies used in the intensification of these treatments in clinical practice. Material and methods: This was a retrospective observational study. Inclusion criteria were patients with UC who received biological treatment during the study period (in 2018). Variables collected were sex, age, number of years diagnosed, intestinal inflammation marker (calprotectin (CF)) before and after treatment, biological drug received during the study period, use of intensification and strategy used (dose increase or dosage interval shortening and determination of drug levels). Loss of response was defined as therapeutic levels not achieved in the case of infliximab (IFX) and adalimumab (ADA). Data were obtained from the outpatient dispensing programme (ATHOS) and the electronic medical records (Diraya). Results: During the study period, 48 patients were included: 61.54% women, median age 41 years (range 19–64) and median number of years diagnosed 7 years (range 1–29). Median CF before starting treatment was 513.95 (range 128–4257) and after biological treatment it was 97 (range 8–3963). The prescribed biological drugs were IFX in 53.06% of patients (n=26), ADA in 22.44% (n=11), vedolizumab (VDZ) in 14.29% (n=7), tofacitinib in 4.08% (n=2) and ustekinumab in 4.08% (n=2). Treatment was intensified in 46.93% of patients (IFX n=16; ADA n=1; VDZ n=6) due to loss of response. In all patients the intensification strategy was to shorten the dosing interval except in two cases in whom the dose was increased (IFX n=2). Intensification strategies in patients receiving IFX and ADA were carried out according to the drug levels obtained, while for VDZ it was performed according to signs of clinical activity and intestinal inflammation markers, such as CF. Conclusion and relevance: Biological drugs represent an effective and safe option in patients with UC but in approximately half of the cases in the study period, treatment had to be intensified. Therefore, the introduction into clinical practice of monitoring serum levels of biological drug is essential for a correct intensification strategy. References and/or acknowledgements: No conflict of interest.